Female-germline specific protein Sakura interacts with Otu and is crucial for germline stem cell renewal and differentiation and oogenesis - Azali Azlan; Li Zhu; Ryuya Fukunaga (eLife)
During oogenesis, self-renewal and differentiation of germline stem cells (GSCs) must be tightly regulated. The Drosophila female germline serves as an excellent model for studying these regulatory mechanisms. Here, we report that a previously uncharacterized gene CG14545, which we named sakura, is essential for oogenesis and female fertility in Drosophila. Sakura is predominantly expressed in the ovaries, particularly in the germline cells, including GSCs. sakura null mutant female flies display rudimentary ovaries with germline-less and tumorous phenotypes, fail to produce eggs, and are completely sterile. The germline-specific depletion of sakura impairs Dpp/BMP signaling, leading to aberrant bag-of-marbles (bam) expression, resulting in faulty differentiation and loss of GSCs. sakura is also necessary for normal levels of piwi-interacting RNAs (piRNAs) levels and for female-specific splicing of sex-lethal (sxl), a master regulator of sex identity determination. We identified Ovarian Tumor (Otu) as a protein binding partner of Sakura and found that loss of otu phenocopies loss of sakura in ovaries. Thus, we identify Sakura as a crucial factor for GSC renewal and differentiation and oogenesis, and propose that Sakura and Otu function together in these processes.